PolaPemberdayaanKelompokTaniMelaluiPengembanganKetrampilanPeningkatanNilaiJualKripikKetelaDengan Varian Rasa Moderen - BAMBANG TRI KURNIANTO (Univeritas Tulungagung, 2020)
ABSTRACK Cassava is one of the commodities that are widely planted by farmers in Indonesia, they choose to plant cassava because it is a type of commodity that has been grown from generation to generation. So that farmers feel that by planting cassava they do not have to bother anymore to learn with new commodities. However, currently, cassava has a fairly low selling value, the bargaining value that is marketed is also considered to have decreased and this does not provide a good profit for farmers. For this reason, the government is trying to provide skills to farmers through farmer groups in an effort to increase the selling value of the cassava itself. Many things can be done so that the sweet potato has a higher selling value when compared to selling it raw. This can be done by producing cassava into cassava chips with new flavor variants that can attract public interest, especially among millennial youth. Various flavors are one of the determining factors for young people to feel curious and make it their favorite food. Keywords: yams, farmer groups, group empowerment